2021
DOI: 10.1007/s00726-021-02981-1
|View full text |Cite
|
Sign up to set email alerts
|

Proline metabolism and transport in retinal health and disease

Abstract: The retina is one of the most energy-demanding tissues in the human body. Photoreceptors in the outer retina rely on nutrient support from the neighboring retinal pigment epithelium (RPE), a monolayer of epithelial cells that separate the retina and choroidal blood supply. RPE dysfunction or cell death can result in photoreceptor degeneration, leading to blindness in retinal degenerative diseases including some inherited retinal degenerations and age-related macular degeneration (AMD). In addition to having re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 182 publications
(231 reference statements)
0
28
0
Order By: Relevance
“…This task is fulfilled by regulating biosynthesis (Figure 2) as well as degradation (Figure 3). The amino acids L-arginine, L-ornithine, glycine, L-proline, L-glutamate, and L-methionine [41][42][43] are effective sources. Biosynthesis predominantly follows two different pathways, both producing PUT as starting material for the following reactions (Figure 2).…”
Section: Biosynthesis Of Polyaminesmentioning
confidence: 99%
“…This task is fulfilled by regulating biosynthesis (Figure 2) as well as degradation (Figure 3). The amino acids L-arginine, L-ornithine, glycine, L-proline, L-glutamate, and L-methionine [41][42][43] are effective sources. Biosynthesis predominantly follows two different pathways, both producing PUT as starting material for the following reactions (Figure 2).…”
Section: Biosynthesis Of Polyaminesmentioning
confidence: 99%
“…The use of well-differentiated RPE cells has been underscored by many studies. Specific to metabolism, studies have shown that, unlike native RPE, poorly differentiated ARPE-19 as well as human telomerase reverse transcriptase RPE-1 cells are incapable of utilizing the amino acid proline as a nutrient source ( 17 , 48 ). Our current study demonstrates a clear link between RPE differentiation and mitochondrial-related metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that proline was decreased along with changes in the glutathione pathway in the plasma of CNV rats. Likewise, previous plasma metabolomics studies of patients with AMD identified significant changes in the proline level . RPE cells prefer proline as a major metabolic substrate. , Proline metabolism is sufficient to fuel mitochondrial metabolism, sustain differentiation, promote GSH synthesis, and protect the RPE against oxidative damage. , Therefore, proline may serve as a protective factor against AMD development.…”
Section: Discussionmentioning
confidence: 90%
“…Blocking of proline metabolism in RPE impairs glucose metabolism and GSH production, which would lead to oxidative damage to the RPE. 25,26 Under conditions of oxidative stress, plasma GSH concentrations are markedly reduced due to a combination of enhanced degradation and decreased synthesis. 29 Consequentially, dietary proline was found to improve visual function in an RPE-specific oxidative damage mouse model.…”
Section: ■ Discussionmentioning
confidence: 99%